Study of the impact of landfill on the health and population living conditions, residing in the settlements adjacent to the landfills - Stankevych, V.V.; Tetenоva, I.O.; Trakhtenherz, H.A. (Environment & Health, 2023)
Objective: To determine the influence of landfills (by the example of landfill of municipal solid waste - MSW, located near the village of Kriukivshchyna, Kyiv oblast) on health and living conditions of the population in nearby villages.Materials and methods: The study was performed as per standardized procedures. Data analysis of morbidity of population according to statistical reporting was conducted in 3 localities. For the independent assessment of the health status of residents in areas adjacent to the dumping of solid waste a questionnaire was developed and a survey of the population (89 questionnaires) conducted.Results: Analysis of the data on the incidence in the population, residing in the settlements adjacent to the landfills, showed that a negative impact of the landfills on the environment significantly affected the living conditions of the population, including health parameters.It was found that the level of morbidity of the population with cardiovascular diseases, respiratory diseases, infectious diseases in villages adjacent to the sites of MSW removal, on average 1.5-2.0 times higher than the similar average regional indicators. At the same time, there is a tendency of increase of incidence rates by 1.4-2.3 times with decreasing distance from the settlement to the landfill from 960 m to 500 m.A sociological survey of the population according to the questionnaire developed by us (89 respondents) showed that the majority of the population assesses the state of the environment in their settlement and the surrounding area as unsatisfactory, linking it with the impact of the landfill, and also notes that functioning near landfill settlement has a negative impact on their health and living conditions.
Keywords: landfill; impact on the environment; morbidity; sociological survey; living conditions